Supervision of the School Principal and Teacher’s Work Motivation Towards Teachers’ Work Discipline - Pramusinto, Bambang; Destiniar, Destiniar; Ahyani, Nur (Journal of Social Work and Science Education, 2023)
This study aims to determine the effect of principal supervision and teacher work motivation on the work discipline of high school teachers in Tanjung Lubuk District. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study was a total of all high school teachers in Tanjung Lubuk District, consisting of 96 teachers. data collection technique using a questionnaire. Data analysis techniques using quantitative descriptive analysis techniques, and multiple regression. The results of this study state that 1) there is a significant effect of the supervision of school principals on the work discipline of high school teachers in Tanjung Lubuk District; 2) there is a significant effect of teacher work motivation on the work discipline of high school teachers in Tanjung Lubuk District; 3) there is a jointly significant effect of the supervision of the principal and work motivation on the work discipline of high school teachers in Tanjung Lubuk District.